2021
DOI: 10.3389/fimmu.2021.596646
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Sema4D in Plasma of Head and Neck Squamous Cell Carcinoma Patients Is Associated With Underlying Non-Inflamed Tumor Profile

Abstract: Semaphorin 4D (Sema4D) is a glycoprotein that is expressed by several tumors and immune cells. It can function as a membrane bound protein or as a cleaved soluble protein (sSema4D). We sought to investigate the translational potential of plasma sSema4D as an immune marker in plasma of patients with head and neck squamous cell carcinoma (HNSCC). Paired peripheral blood and tumor tissue samples of 104 patients with HNSCC were collected at the same time point to allow for real time analysis. Scoring of the histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 45 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…Tumor cells-derived Sema4D promorted tumor growth and vascularity, as well as assisted immune escape by inducing MDSCs expansion (Younis et al 2016). Rania H and his colleagues (Younis et al 2021) revealed that most HNSCC patients had higher sSema4D level in plasma, which correlated to the histological immune excluded subtype. With regard of distant metastasis, Sema4D enhanced skeletal metastasis and represent a new therapeutic target in breast cancer and lung cancer (Yang et al 2016;Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells-derived Sema4D promorted tumor growth and vascularity, as well as assisted immune escape by inducing MDSCs expansion (Younis et al 2016). Rania H and his colleagues (Younis et al 2021) revealed that most HNSCC patients had higher sSema4D level in plasma, which correlated to the histological immune excluded subtype. With regard of distant metastasis, Sema4D enhanced skeletal metastasis and represent a new therapeutic target in breast cancer and lung cancer (Yang et al 2016;Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It interacts with T cells and B cells by binding CD72 [ 11 ], interacts with endothelial cells by binding PlexinB1 [ 33 ], and activates endothelial differentiation through the ERK and AKT pathways [ 34 ]. Soluble Sema4D levels in plasma may be regarded as a biomarker in head and neck squamous cell carcinoma [ 35 ], and high levels of soluble Sema4D are associated with the INF- γ -negative tumor microenvironment [ 27 ]. Our previous study also showed high soluble Sema4D levels in the blood [ 29 ], and in this study, we found that soluble Sema4D is positively correlated with Sema4D expression in PBMCs but not in BMMCs, as the serum was collected from peripheral blood, not from bone marrow, it is not surprising soluble Sema4D is only correlated with Sema4D expression in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Sema4D is also involved in immune response by interacting with the tumor microenvironment; soluble Sema4D level has been found to increase when coculturing with tumor-associated macrophages in a gastric carcinoma cell line [ 20 ]; the function of CD8+ T cell is inhibited when it fails to release soluble Sema4D in non-small-cell lung cancer [ 26 ]; in addition, inhibition of myeloid-derived suppressor cells is associated with Sema4D secretion in human head and neck squamous cell carcinoma [ 16 ]. As soluble Sema4D plays an important role in interacting with the tumor microenvironment, its levels in plasma are regarded as a biomarker of poor prognosis in head and neck squamous cell carcinoma [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study with murine rhabdomyosarcoma showed that CXCR2-positive MDSCs inhibited the antitumor effect of anti-PD-1 antibody treatment and that anti-CXCR2 monoclonal antibody therapy enhanced it ( 30 , 31 ). It has been reported that Sema4D induced MDSC in the tumor microenvironment ( 32 ) and that head and neck squamous cell carcinoma patients with high plasma Sema4D levels had less infiltration of immune cells into the tumor microenvironment ( 33 ). Experiments with murine oral cancer-1 showed that Sema4D Ab combined with either CTLA-4 or PD-1 blockade enhanced tumor rejection or delayed tumor growth ( 34 ).…”
Section: Discussionmentioning
confidence: 99%